Administrative model for Sekolah Agama Rakyat (SAR): excellence practices / Mohd Nasir Ayub ... [et al.] - Ayub, Mohd Nasir; Noordin, Nazmi@Nazni; Mohamed Sawal, Mohd Zool Hilmie; Mat Hassan, Surita Hartini (2021)
People's Islamic Religious School (PIRS) or Sekolah Agama Rakyat (SAR) in Malaysia is a nonsponsored religious school that needs a paradigm shift to become more visible and luminous in the national education system. The management of a school that is not guided by an effective administrative model will affect the school excellence. The continuity of the school's excellent performance depends heavily on the efficiency and effectiveness of the SAR administration. Generally, most of the SAR administration are based on each administrator's discretion without relying on one common acceptable model for all SAR. Therefore, only a handful of SAR manage to excel in their operations. This study is done in order to identify the administrative practice and the challenges faced by SAR administrators in managing the SAR, based on these scenarios. Eight SAR administrators in three northern states of Peninsular Malaysia (namely Kedah, Penang, and Perlis) were interviewed individually using semi structured questions in this qualitative research. Data collected from the interview were then analysed with Atlas t.i version 8 (AV8) content analysis software. Findings indicated six administrative practices commonly adopted by selected SAR's administrators that makes them the finest and most outstanding SAR administrators of their respective states. The findings also suggested one administrative model that could be used by all SAR as a guide to ensure smoothness and excellence of each SAR in order to produce and develop great leaders of the future with Islamic teachings as its root.